(untitled) (Fiep Bulletin - online, 2014)
Track and Field is a sportive modality that can be studied, practiced and adapted to all school levels. This study aimed to propose a teaching methodology of school athletics from the use of materials as alternative resources. Future teachers will be encouraged to use their creativity during the teaching activities or it will be promoted a greater interest in the dissemination and practice of athletics, in the schools. Also, this could allow the development of preservationist awareness among students and teachers in order to meet the requirements of the XXI century society. The used methodology was characterized as explanatory, descriptive and based on a quasi-experimental model, with qualitative and quantitative features, involving bibliographic researches and field trips. In the case of this research, the population and sample are equals due to the small number of the first one. Then, the sample consisted of the student’s community of the 1st year, registered in the subject on Athletics Methodology, and the 4th year’s students that already studied it, in the Bachelor’s Degree Course on Physical Education, at UNIVILLE. There were 159 participants. It was possible to develop and apply two duly validated questionnaires that could provide grants in order to support the legal character of this research. It was found that the current reproductivism has significantly restricted the initiative and creativity of Physical Education teachers, leading them to teach methods that might be practiced with no or minimal material, and almost always a ball. Thus, the vast majority of teachers need a continuing education. They consider as good enough the content learned, in the under graduation, to teach their classes. This lack of interest was supported by the contents’ reproduction easiness, which did not receive any innovation, and they are not suitable to motivate the practice of physical activities.